Comparative transcriptome analysis reveals the potential mechanism of GA3-induced dormancy release in Suaeda glauca black seeds - Wang, Hongfei; Xu, Tianjiao; Li, Yongjia; Gao, Rui; Tao, Xuelin; Song, Jieqiong; Li, Changping; Li, Qiuli (Frontiers in Plant Science, 2024)
Suaeda glauca Bunge (Bunge) produces dimorphic seeds in the same plant, including brown seeds with non-dormant characteristics and black seeds with intermediate physiological dormancy traits. Previous studies showed that black seeds exhibited very low germination rate in natural conditions, and exogenous GA3 effectively enhanced the germination rate of black seeds. However, the physiological and molecular mechanism underlying the effects of GA3 on S. glauca black seeds is still unclear. In this study, transcriptomic profiles of seeds at different germination stages with and without GA3 treatment were analyzed and compared, and the TTF, H2O2, O2 -, starch and soluble sugar contents of the corresponding seed samples were determined.The results indicated that exogenous GA3 treatment significantly increased seed vigor, H2O2, and O2 -contents, but decreased starch and soluble sugar contents of S. glauca black seeds during seed dormancy release. RNA-Seq results showed that a total of 1136 DEGs were identified in three comparison groups, and involved mainly in plant hormone signal transduction, diterpenoid biosynthesis, flavonoid biosynthesis, phenylpropanoid biosynthesis and carbohydrate metabolism pathway. Among them, the DEGs related to diterpenoid biosynthesis (SgGA3ox1, SgKAO, SgGA2ox8) and ABA signal transduction (SgPP2Cs) could play important roles during seed dormancy release. Most genes involved in phenylpropanoid biosynthesis were activated under GA3 treatment conditions, especially many SgPER genes encoding peroxidase. In addition, exogenous GA3 treatment also significantly enhanced the expression of genes involved in flavonoid synthesis, which might be beneficial to seed dormancy release. In accordance with declined in starch and soluble sugar contents, and 15 genes involved in carbohydrate metabolism were significantly up-regulated during GA3 induced dormancy release, such as SgBAM, SgHXK2, and SgAGLU etc. In a word, exogenous GA3 effectively increased the germination rate and seed vigor of S. glauca black seeds by mediating the metabolic process /or signal transduction of plant hormone, phenylpropanoid and flavonoid biosynthesis, and carbohydrate metabolism procession. Our results provide novel insights into the transcriptional regulation mechanism of exogenous GA3 on the dormancy release of S. glauca black seeds. The candidate genes generated in this study may further be studied, and used to enrich our knowledge of seed dormancy and germination.